Integrasi Kearifan Lokal sebagai Strategi Penguatan Pembelajaran Mendalam pada PAUD - Elinda Suer (Muara Aksara: Jurnal Ilmiah Multidisipliner, 2026)
The Merdeka Curriculum is an educational policy that provides flexibility for educational institutions to design learning that is contextual, relevant, and student-centered. At the Early Childhood Education (ECE) level, the implementation of this curriculum emphasizes play-based learning, exploration, and character development through the Pancasila Student Profile. This study aims to analyze the integration of local wisdom as a strategy to strengthen deep learning in the implementation of the Merdeka Curriculum in early childhood education. The research method used is a literature review with a descriptive qualitative approach. Data were obtained through the analysis of various scientific sources such as national and international journals, academic books, and relevant educational policy documents. The results of the study indicate that the integration of local wisdomuch—as traditional games, folklore, local languages, and community cultural practices—can serve as contextual learning resources that support joyful, meaningful, and mindful learning. In addition, the integration of local wisdom contributes to strengthening children's character, cultural identity, and socio-emotional development. Therefore, local wisdom-based learning can be an effective strategy to support the implementation of the Merdeka Curriculum in early childhood education institutions.